Shot hole disease on Prunus laurocerasus caused by Neofusicoccum parvum in Serbia. Issue 6 (5th July 2016) - Zlatković, M.; Keča, N.; Wingfield, M. J.; Jami, F.; Slippers, B.
Summary: Between 2010 and 2014, symptoms of a shot hole disease were observed on cherry laurel ( Prunus laurocerasus L.) trees and shrubs in parks and other public plantings in Belgrade, Serbia. Ten symptomatic leaves were collected from each of the diseased plants and the associated fungus isolated and identified using multigene phylogenetic analyses and asexual morphological characters. The pathogen was identified as Neofusicoccum parvum . The same symptoms were produced when the pathogen was inoculated on test plants. To the best of our knowledge, this is the first report of N. parvum causing shot hole disease on P. laurocerasus .